THE INTERSECTION OF PEDAGOGY AND TECHNOLOGY: A COMPREHENSIVE GUIDE TO CAREERS IN EDUCATIONAL AI AND DIGITALIZATION - SantoshKumar Pulijala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article provides a comprehensive overview of career opportunities at the intersection of digitalization, artificial intelligence (AI), and public education. As educational systems increasingly adopt digital technologies and AI-driven solutions, there is a growing demand for professionals who can navigate this complex landscape. The article explores key competencies required for success in this field, including technical skills in programming, data science, and AI, as well as pedagogical knowledge and ethical considerations. It outlines various career pathways, such as educational technologist, AI engineer, data analyst, and policy advisor, detailing the roles and responsibilities of each. The article also addresses the challenges facing the integration of AI in public education, including equity issues, teacher training, and long-term sustainability. By synthesizing current trends, skill requirements, and ethical considerations, this work serves as a valuable guide for individuals seeking to leverage technology to improve educational outcomes in the public sector. The findings underscore the importance of continuous learning and networking in this rapidly evolving field, highlighting the potential for innovative professionals to significantly impact the future of public education through the thoughtful application of digital and AI technologies.